Related Factors of Response Time in Handling Head Injury in Emergency Unit of Prof.Dr.H.M.Anwar Makkatutu Bantaeng General Hospital - Satrial Mudatsir; Moh. Syafar Sangkala; Andina Setyawati (Indonesian Contemporary Nursing Journal, 2017)
Introduction: The mechanisms of nurse response time in handling head injury patients has an important role on the safety and viability of patients in reference to the rules of “safety and time saving is life saving”. The purpose of the study: This study aims to identify factors that related to the response time in handling head injury patient in emergency department (ED) and to determine the most related factor  to the response time. Method: This study was an observation design and using cross sectional approach. A total sample of 32 emergency department nurses participated for this study, in references to the inclision and exclusion criteria. The data were analyzed by using chi-square, Fisher's extract test and logistic regression. Result: This study found that there were statistical significance between respon time and  level of education (p = 0.006), duration of working (p = 0.005), medical emergency training (p = 0.001), the emergency department facilities (p = 0.008) and the level of the patient acute condition (p = 0.006). Among the factors, it was found that facilities most related factor to the respon time (OR = 6.945). Conclusion and suggestion: It is concluded that there is a relationship between respon time and education level, work duration of nurses, medical emergency training, Emergency facilities and the patient acute condition  in handling head injury patients and facilities are the factors that most related to the response time handling head injury. It is suggested to the hospital to complete the emergency room facilities because the facilities affects the response time handling head injury patients.